2021
DOI: 10.3389/fimmu.2021.595343
|View full text |Cite
|
Sign up to set email alerts
|

In Nasal Mucosal Secretions, Distinct IFN and IgA Responses Are Found in Severe and Mild SARS-CoV-2 Infection

Abstract: Likely as in other viral respiratory diseases, SARS-CoV-2 elicit a local immune response, which includes production and releasing of both cytokines and secretory immunoglobulin (SIgA). Therefore, in this study, we investigated the levels of specific-SIgA for SARS-CoV-2 and cytokines in the airways mucosa 37 patients who were suspected of COVID-19. According to the RT-PCR results, the patients were separated into three groups: negative for COVID-19 and other viruses (NEGS, n = 5); negative for COVID-19 but posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…We observed that only some patients had S1-specific IgA in the nasal cavity while almost none had IgG, the magnitude of the response was lower than the one measured in serum. These heterogeneity of the S1-specific IgA levels at the mucosa has been recently reported by others [ 48 – 50 ]. IgA is important for early neutralization of SARS-CoV-2 in blood and saliva [ 41 ].…”
Section: Discussionsupporting
confidence: 80%
“…We observed that only some patients had S1-specific IgA in the nasal cavity while almost none had IgG, the magnitude of the response was lower than the one measured in serum. These heterogeneity of the S1-specific IgA levels at the mucosa has been recently reported by others [ 48 – 50 ]. IgA is important for early neutralization of SARS-CoV-2 in blood and saliva [ 41 ].…”
Section: Discussionsupporting
confidence: 80%
“…IgG in combination with IgM and IgA would have greater neutralization capacity than IgG alone, a broader repertoire of antibodies correlates with a stronger SARS-CoV-2 neutralization [22]. Initial IgA plasmablast's response declines quickly, whereas IgA-producing plasma cells persist for years in mucosae [23]. It might explain that individuals mounting a strong IgA response would seem to loose antibodies, but it will be interesting to check out whether salivary IgA remains positive or not so far IgA antibodies are the major component of the neutralizing antibodies developed in response to SARS-CoV-2 infection [24] Lower lymphocyte counts and higher neutrophils and as well higher seric IgA would help predict future negativization of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation in mucosal immunity research is the inaccuracy of the results due to mucosal sample collection methods, such as, the nasal swabs or irrigation methods, which are subjected to low sample yield and inconsistency of the dilution effect. 20, 21 In our study, conjunctival fluid (CF) samples were collected with a technique similar to the Schirmer’s test 22, 23 while the nasal epithelial lining fluid (NELF) samples were collected by nasal strips. 24, 25 These methods are standardised and exhibit extended sample stability even when stored at room temperature, 26 which ensure sample validity.…”
Section: Mainmentioning
confidence: 99%